Transformation of Digital Legal Deposit in Terms of Legislation and Public Access - Möldre, Aile; Felt, Kairi (Knygotyra, 2018)
[full article, abstract in English; abstract in Lithuanian] The article treats the development of commercial e-book publishing in Estonia from the publishers’ perspective. The data is collected by surveys and interviews carried out among publishers in 2016. The results reveal that the main hindrances like the limited size of the Estonian-language e-book market, the readers’ preference for printed books as well as nonprofitability of e-books had remained the same compared to the study by Helen Reiser from 2011. The availability and affordability of different reading devices, on the contrary, had ceased to be a barrier to e-book production according to the publishers’ perceptions. The publishers value their first experiences with e-books and wish to secure their image as e-book publishers, although they do not predict a rapid increase in the production. Perceptions of the e-book market drivers and barriers of the Estonian publishers are similar to the attitudes of publishers from other small-language markets like Sweden, Lithuania and Croatia.